Demography, Aging, and Mobility in the ECA Region : A Critical Overview of Trends and Future Challenges - Heleniak, Timothy (World Bank, Washington, DC, 2016)
The countries of the Europe and Central Asia (ECA) region are confronting a number of demographic challenges over the coming decades. These include shrinking populations and labor forces because of below replacement-level fertility and older age structures, high mortality in a large portion of the region, aging populations and high dependency ratios, shrinking youth populations and less new entrants to the labor force, and relatively immobile populations. The report is structured as follows. After this introduction, the second section reviews population trends in the ECA region over the past two decades. Following that is a review of the literature on the issue of aging globally and specifically in the ECA region. This includes the implications of population aging on economic growth and, employment, and public expenditures. The next section looks at projections of demographic trends in the ECA region for the period 2010 to 2040, including aging trends. Following this is an examination of the role that migration and mobility play in the aging process among the ECA countries in the future. The final section concludes by discussing policy options and areas for further research and analysis